Prospective analysis of delirium risk in geriatric femur fracture patients using the Nottingham Hip Fracture Score - S. Shankar; J. Shyamprakash; K. Narayanasamy (Journal of Geriatric Mental Health)
Background: Delirium is a common and serious complication in geriatric patients following femur fractures, yet risk stratification remains understudied. Identifying modifiable risk factors is critical for improving clinical outcomes. Methods: This prospective observational study enrolled 30 elderly patients (aged ≥65 years) with acute femur fractures at a single institution. Delirium risk was assessed using the Nottingham hip fracture score (NHFS), alongside variables including age, gender, cognitive status (evaluated through standardized tools, e.g., Confusion Assessment Method [CAM]), comorbidities, medication use, and hemoglobin (Hb) levels. For cognitively impaired patients, written informed consent was obtained from caregivers to ensure ethical inclusion. Results: Participants were stratified into two age groups: 66–84 years (n = 18, 60%; mean age 70.22 ± 3.96) and ≥85 years (n = 12, 40%; mean age 86 ± 1.6). A majority (86.67%, n = 26) demonstrated significant cognitive impairment (MMSE score <6; mean 3.23 ± 1.07). All participants were institutionalized, with 53.33% female, 60% having ≥1 comorbidity, and 40% presenting with Hb <10 g/dL. Multiple linear regression revealed that age negatively correlated with CAM scores (β = −0.31, P = 0.041), whereas higher NHFS scores predicted increased delirium risk (β =0.59, P < 0.001). The model explained 57.38% of the variance in delirium risk (R² =0.5738). Conclusion: Age, cognitive impairment, and elevated NHFS scores are significant predictors of delirium in geriatric femur fracture patients. These findings underscore the need for early, targeted interventions (e.g., optimizing Hb levels and managing comorbidities) to reduce delirium risk in this vulnerable population.